PELATIHAN KEAMANAN CYBER UNTUK ANAK-ANAK DAN ORANG TUA DI MESJID IKHSAN KOTO SIBAUAK - Nurmaliana Pohan; Juna Eska; Hidayatullah Hidayatullah (Smart Education, 2024)
Abstarct : In the increasingly developing digital era, internet use has become an inseparable part of everyday life. However, with the convenience offered by technology, there are also various cyber security risks that can endanger children and the elderly. To address this problem, the